Контроль складу плазми магнетроного разряду методом атомно-емісійної спектроскопії - Маковська, О. Г. (ХНУРЕ, 2021)
The schemes for measuring the relative emission spectra of the magnetron discharge plasma and the design of the adapter for inputting the optical signal into the measuring circuit to control the sputtering process have been developed. The design takes into account the high sensitivity of the spectrophotometer and protects the entrance window from contamination by sprayed material
Keywords: плазма; магнетроний разряд